Recent advances on peptide‐based theranostic nanomaterials. Issue 4 (23rd July 2020) - Rong, Lei; Lei, Qi; Zhang, Xian‐Zheng
Abstract: Theranostic nanomaterial, which amalgamates diagnosis and therapy of diseases into one nanosystem, has become one of the core interests in nanomedicine research. Functional peptides can be integrated into theranostic nanomaterials and endow them with special properties to accomplish much more complicated biomedical tasks. Peptide‐based theranostic nanomaterials can be formulated with specific targeting, transmembrane delivery, and stimulus response. In this Minireview, we describe general ideas of fabricating peptide‐based theranostic nanomaterials, concerning the design and variegated biomedical applications, and highlighting their advances during the past 5 years. Abstract : Peptide‐based theranostic nanomaterials integrate functional peptides into theranostic nanomaterials, which endow them with various advantages of peptides including targeting, intracellular delivery, and stimuli response. This mini‐review describes general ideas of fabricating peptide‐based theranostic nanomaterials, concerning the design and variegated biomedical applications during the past 5 years.